In Silico Characterization of a Novel Bioactive Compound derived from Psidium guajava 4-[5-(Pyridin-4-yl)-1,2,4-oxadiazol-3-yl]-1,2,5-oxadiazol-3-amine: A Potential Inhibitor for Targeting Signaling Proteins involved in Diabetes Development (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Pharmacological interventions for diabetes predominantly involve chemically synthesized compounds, often causing undesirable side effects. This has led to a growing interest in plant-based therapeutic alternatives. Technological advancements have facilitated the discovery of bioactive phytochemicals with medicinal properties. This study employs molecular docking analysis to assess the anti-diabetic potential of a naturally derived compound, 4-[5-(Pyridin-4-yl)-1,2,4-oxadiazol-3-yl]-1,2,5-oxadiazol-3-amine (POA), obtained from Psidium guajava leaf extract. The evaluation focuses on its inhibitory action against four human proteins 11 β -HSD1 (PDB: 4K1L), GFAT (PDB ID: 2ZJ4), SIRT6 (PDB ID: 3K35) and Aldose reductase (PDB ID: 3G5E) associated with diabetes. Physicochemical, pharmacokinetic, and ADMET profiles were computed using online web servers Molinspiration, ADMETLAB 2.0, and SWISSADME. POA demonstrated superior binding affinity (in Kcal/mol) -8.0, -7.5, -8.9 and -9.5, respectively) compared to the widely used diabetic drug Metformin -5.4, -6.0, -5.4 and -7.2 with these receptor proteins. Based on molecular docking studies and pharmacokinetics/ADMET profiles, POA may act as a multi-targeted, less harmful, and more efficacious medication for Type 2 Diabetes Mellitus (T2DM) compared to Metformin.